Evaluation of fetal middle cerebral artery doppler and umbilical artery doppler as predictors of perinatal outcome in small for gestational age fetuses - Jamil, Amilia Afzan Mohd (Universiti Sains Malaysia, 2011)
Doppler is one of the means used for in-utero monitoring of high risk pregnancy. It can provide useful information pertaining to the in-utero condition of fetuse with growth restriction, in high risk pregnancy and post-date pregnancy with oligohydromnios. Since its introduction in the field of obstetrics and gynaecology by Fitzgerald and Drumm in 1977, many studies were conducted to assess its sensitivity and specificity as an antenatal monitoring tool. In Hospital Universiti Sains Malaysia, Doppler study was used on a daily basis in management of high risk pregnancy. To evaluate the diagnostic performance of fetal middle cerebral artery (MCAPI), and umbilical artery (UA) Doppler Ultrasonography (US) as predictors of adverse perinatal outcome in Small for Gestational Age fetuses. Diagnostic Prospective Cross-Sectional Study This study was conducted in Hospital University Science Malaysia from October 2009 till October 2010. 72 patients were enrolled in the study after fulfilling the inclusion criteria. 70 (97.2%) patients were Malays and 1 was Chinese and 1 was Burmese. The mean patients’ age was 30.76 +7-6.294 years. The mean weight, height and body mass index was 53.05kg, 152.81cm and 22.66kg/m2 respectively. 45 (62.5%) patients had medical problems, whereby 30 (41.6%) of them had hypertension and its complication related to pregnancy. 6 (8.3%) had diabetis mellitus in which 2 of them had pre-existing diabetes diagnosed before pregnancy. 51 (70.8%) patients had normal Umbilical Artery Pulsatility Index (UAPI) and Middle Cerebral Artery Pulsatility Index (MCA PI), 4 (5.7%) patients had normal UA PI but abnormal MCA PI. 11 (15.2%) patients had both abnormal UA PI and MCA PI. The mean PI for normal umbilical artery Doppler was 0.91 +/- 0.18, the mean PI for suspicious umbilical artery Doppler was 1.33 +/- 0.11, and the mean PI for pathological umbilical artery Doppler was 3.11 +/- 0.76. The mean PI for normal Middle Cerebral Artery (MCA) Doppler was 1.41 +/- 0.32 and the mean PI for pathological MCA Doppler was 1.04 +/- 0.19. The mean gestational age at delivery was 36+/- 3.095. 25 patients underwent emergency lower segment Caesarean Section, 7 neonates had major adverse perinatal outcome, specifically necrotizing enterocolotis. 70 babies had APGAR score of more than 7 at 5 minutes, however, all babies had normal umbilical cord pH at birth. 12 babies needed intubation and admission to NICU and 2 babies had Early Neonatal Deaths due to extreme prematurity and sepsis. In this study, Umbilical Artery Pusatility Index (UA PI) is more sensitive, more specific and had more positive and negative predictive value compared with MCA PI and MCA/UA PI ratio. UA PI had a sensitivity of 55.5%, specificity 95.5%, positive predictive value of 88.2% and negative predictive value of 78.1%. While an abnormal UA PI is a better predictor of adverse perinatal outcome than an abnormal MCA PI and MCA/UA PI ratio, a normal MCA PI may help to identify fetuses without major adverse perinatal outcome. The 2 method used in combination had a better diagnostic and monitoring value. Base on the cord blood pH recorded in this study, the decision for early intervention was decided much before the fetus suffered any form of acidosis. It can be concluded that the caesarean section rate can be reduce further, by supporting the decision to deliver early base on combination of the Doppler finding and biophysical profile score as well as the clinical assessment.